1997
DOI: 10.1017/s1357729800015599
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resistance of different genotypes of sheep to natural infections with gastro-intestinal nematodes

Abstract: During a 3-year period, from April 1991 to December 1993, in a flock with four lambing periods annually, faecal samples from lambs at weaning at the age of 3 months (no. = 1756), were examined for gastro-intestinal nematode eggs by the McMaster method. Faecal samples were also examined at the age of 9 (no. = 170), 12 (no. = 157), 15 (no. = 253) and 18 (no. = 85) months from the females only. From June to December 1993 packed cell volume (PCV) was also examined from lambs at weaning. Seven genotypes were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…However, the reliance on such usage has come at a price: of anthelmintic resistance . In providing options for sustainable control methods which are less reliant on anthelmintics, considerable focus has been given to breeding animals displaying natural resistance to GIN . These approaches have generally been successful in identifying resistant genotypes based on phenotypic markers such as faecal egg count (FEC) and either plasma or saliva antibody levels , with a moderate‐to‐high heritability consistently reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reliance on such usage has come at a price: of anthelmintic resistance . In providing options for sustainable control methods which are less reliant on anthelmintics, considerable focus has been given to breeding animals displaying natural resistance to GIN . These approaches have generally been successful in identifying resistant genotypes based on phenotypic markers such as faecal egg count (FEC) and either plasma or saliva antibody levels , with a moderate‐to‐high heritability consistently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic identification of resistant animals through molecular techniques such as quantitative trait loci, genomewide associated studies and candidate gene analysis has also been successful and has been suggested as a more reliable approach than use of more traditional phenotypic markers . Immunity to gastrointestinal parasites is known to be multigenic, with numerous candidate genes suggested based on evaluation of selection lines of sheep for divergence in immune competence or from breeds of animals noted for their ability to resist parasite infections . Nevertheless, immunity is not binary and regardless of genotype, animals show considerable variation in the timing and magnitude of immunological responses to GIN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are also fighting type sheep, so called garut sheep. Indonesian thin and fat tail sheep have several advantages; especially they are well adapted to the hard environment, able to utilize low-quality feed, prolific (Inounu et al, 1986), early puberty (Sutama et al, 1988) and resistance to internal parasites (Romjali et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Variation has been observed both among the animals of the same breed and between animals from different breeds in their resistance to parasite infections (Stear and Murray, 1994;Romjali et al, 1997). Special attention is paid in the studies on this variation to the major histocompatibility complex (MHC) (Beh and Maddox, 1996).…”
Section: Introductionmentioning
confidence: 99%